2009
DOI: 10.1016/j.jcf.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic enzyme replacement therapy for young cystic fibrosis patients

Abstract: Those parents who had a preference favoured CfC over C10. Both enzyme preparations improved malabsorption to a similar degree, although the applied dosages could have been too low in some children reflected in a suboptimal CFA. These data support the use of CfC for young patients with cystic fibrosis improving the daily care of this cohort detected mainly now through neonatal screening programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Subjects aged 2-3 years also showed an increase in these growth parameters, as well as BMI-for-age, although the increases were smaller than in the younger age group, and a slight decrease was observed in height-for-age in this group. Stool frequency observed during treatment was within the range seen in other studies of young children with CF receiving PERT (1.8-2.4 per day) [14][15][16]24] and similar to that found in surveys of healthy children aged 1 to 4 years in the UK (1-2 per day) [25] and aged 1 month to 3 years in Italy (1.4-1.9 per day) [26]. The mean percentage of days without soft/watery stools during treatment in our study (65%), compares favourably with other studies of Creon in young children (N 48% days without soft/watery stools [15] and approximately 60-70% patients without soft/watery stools each day [16]).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Subjects aged 2-3 years also showed an increase in these growth parameters, as well as BMI-for-age, although the increases were smaller than in the younger age group, and a slight decrease was observed in height-for-age in this group. Stool frequency observed during treatment was within the range seen in other studies of young children with CF receiving PERT (1.8-2.4 per day) [14][15][16]24] and similar to that found in surveys of healthy children aged 1 to 4 years in the UK (1-2 per day) [25] and aged 1 month to 3 years in Italy (1.4-1.9 per day) [26]. The mean percentage of days without soft/watery stools during treatment in our study (65%), compares favourably with other studies of Creon in young children (N 48% days without soft/watery stools [15] and approximately 60-70% patients without soft/watery stools each day [16]).…”
Section: Discussionsupporting
confidence: 81%
“…stomatitis, frequent bowel movements, and abdominal pain are known adverse drug reactions associated with Creon treatment [13]. These safety findings compare favourably with other studies assessing Creon in subjects with EPI due to CF, including two studies of Creon Micro in paediatric subjects that had shorter treatment periods of 2 weeks [15] and 8 weeks [14] (overall frequency of AEs 43.6% and 75%, respectively; frequency of treatment-related AEs 7.7% and 8.3%, respectively), and a study of Creon capsules in children b 7 years old with a treatment period of~2 weeks (overall AEs 50%; treatment-related AEs 5.6%) [16]. Although three patients exceeded the highest recommended dose of 10,000 lipase units/kg body weight/day, no cases suggestive of fibrosing colonopathy or other serious events occurred in these patients.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Impairments in fat digestion affect the absorption of the fatsoluble vitamins A, D, E, and K, all of which, together with other PEI-related nutritional deficits, could be associated with complications such as cardiovascular disease, compromised immunity, cancerogenicity, psychological disorders, hypoprothrombinemia, bleeding disorders, night blindness, and muscle weakness [10][11][12]. Early detection of PEI can help prevent malabsorption-/malnutrition-associated complications by enabling expedient treatment with pancreatic enzyme replacement therapy (PERT), which numerous clinical trials have shown to be highly effective, not only in patients with CP, but also following pancreatic surgery, and in children and adults with CF [6,[13][14][15][16]. Clinically, the most common cause of PEI is CP, although symptoms of PEI may not appear until several years after disease onset [17].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic enzyme insufficiency leads to malabsorption of fats, diarrhoea, and failure to thrive, and this is compounded by lung disease and infection, which further increases calorie requirements. Thus recommendations are for early nutritional support with adequate pancreatic replacement management, as this has been shown to improve growth and subsequent lung function (Konstan et al 2003;Munck et al 2009). …”
Section: Clinical Management Of Cfmentioning
confidence: 99%